2017
DOI: 10.3389/fcimb.2017.00502
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Lactobacilli Reduce Neisseria gonorrhoeae Viability through Multiple Strategies: An in Vitro Study

Abstract: The emergence and spread of antimicrobial resistance in Neisseria gonorrhoeae (GC) underline the need of “antibiotic-free” strategies for the control of gonorrhea. The aim of this study was to assess the anti-gonococcal activity of 14 vaginal Lactobacillus strains, belonging to different species (L. crispatus, L. gasseri, L. vaginalis), isolated from healthy pre-menopausal women. In particular, we performed “inhibition” experiments, evaluating the ability of both lactobacilli cells and culture supernatants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 51 publications
(62 reference statements)
6
55
1
Order By: Relevance
“…Considering that untreatable gonorrhea cases might soon become a reality, identifying new prevention and treatment options is crucial. In addition to new antibiotics or a novel combination of the currently used ones, new therapies have been suggested to prevent recurrence of the infection: IL-12 to promote Th1-driven adaptive immune response (34), vaginal lactobacillus strains to counteract gonococcal growth (35), and fatty acid derivatives for a fast anti-gonococcal activity targeting membrane disruption (36). Here we present a potentially novel therapeutic approach that targets a virulence mechanism of bacteria -its ability to bind the complement inhibitor C4BP.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that untreatable gonorrhea cases might soon become a reality, identifying new prevention and treatment options is crucial. In addition to new antibiotics or a novel combination of the currently used ones, new therapies have been suggested to prevent recurrence of the infection: IL-12 to promote Th1-driven adaptive immune response (34), vaginal lactobacillus strains to counteract gonococcal growth (35), and fatty acid derivatives for a fast anti-gonococcal activity targeting membrane disruption (36). Here we present a potentially novel therapeutic approach that targets a virulence mechanism of bacteria -its ability to bind the complement inhibitor C4BP.…”
Section: Discussionmentioning
confidence: 99%
“…A normal vaginal microbiota, dominated by lactobacilli, is crucial for the prevention of several urogenital and sexually transmitted infections, including Chlamydia ( Gupta et al, 1998 ; Spurbeck and Arvidson, 2008 ; Parolin et al, 2015 ; Nardini et al, 2016 ; Foschi et al, 2017 ; Ñahui Palomino et al, 2017 ). This aspect is strengthened by the demonstration that in case of bacterial vaginosis, a clinical condition characterized by the depletion of lactobacilli, a higher risk of STI transmission and acquisition is reported ( Taha et al, 1998 ; Martin et al, 1999 ; Wiesenfeld et al, 2003 ; Abbai et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…To expand our consideration of species-specific differences and explore a potential environment in which DTZ would be clinically useful (the lower female reproductive tract), we tested the efficacy of DTZ against a representative vaginal commensal, Lactobacillus gasseri. L. gasseri has been previously shown to block N. gonorrhoeae-epithelial cell interactions (28,29), and lactobacilli in general maintain a low pH in the vagina that is an important determinant of discouraging Neisseria growth (30). We found that L. gasseri is greatly reduced in sensitivity to DTZ compared to that of N. gonorrhoeae as well as the previously described E. coli and Salmonella enterica (17).…”
mentioning
confidence: 49%
“…Concentrations of 250 and 500 M were able to delay the initiation of growth, although growth proceeded at a normal rate throughout exponential phase, plateauing at a much higher A 540 value than lower-concentration DTZ treatments. Observation of the cultures at the end of growth suggests that the increased optical density is due to biofilm formation (data not shown (30,37). For an antimicrobial agent to be effective against N. gonorrhoeae infection, it will need to function in the context of both interbacterial competition and host cell infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation